2007
DOI: 10.1158/0008-5472.can-06-4249
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytokine Production and Cytotoxic Activity of Human Antimelanoma Specific CD8+ and CD4+ T Lymphocytes by Adenosine-Protein Kinase A Type I Signaling

Abstract: The goal of this study was to investigate the effects of adenosine and its stable analogue 2-chloroadenosine (CADO) on the cytotoxic activity and cytokine production by human antimelanoma specific CD8 + and CD4 + T-helper type 1 (Th1) clones. The cytotoxic activity of CD8 + T cells was inhibited by adenosine and CADO. Using Lab MAP multiplex technology, we found that adenosine inhibits production of various cytokines and chemokines by CD8 + and CD4 + T cells. Studies with CGS21680, a specific agonist of adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 45 publications
9
97
0
1
Order By: Relevance
“…The accumulated studies of cAMP-and PKA-mediated inhibition of T cell functions have demonstrated that cAMP-elevating A2AR agonists inhibit cytotoxic activity through down-regulation of Fas ligand and granule exocytosis (27)(28)(29)(30). A2AR-mediated signaling may down-regulate the very early events of TCR signaling because PKA phosphorylates COOH-terminal Src kinase to inhibit T cell activation by interrupting Lck activation (31).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulated studies of cAMP-and PKA-mediated inhibition of T cell functions have demonstrated that cAMP-elevating A2AR agonists inhibit cytotoxic activity through down-regulation of Fas ligand and granule exocytosis (27)(28)(29)(30). A2AR-mediated signaling may down-regulate the very early events of TCR signaling because PKA phosphorylates COOH-terminal Src kinase to inhibit T cell activation by interrupting Lck activation (31).…”
Section: Discussionmentioning
confidence: 99%
“…As control, CFSE-labeled clones 11/4 and 4/43 were also incubated with TRAG-3-specific CD4 + Th clone 62/8 or NY-ESO-1-specific CD4 + T cell clone 107/5, respectively. Clones 11/4 and 4/43 were previously described (16,17). Clone 11/4 was tested in cytokine production assays and CFSE proliferation assays to confirm its Th functions.…”
Section: Il-2 Suppression Assaysmentioning
confidence: 99%
“…The present study did not investigate the ability of PGE 2 to inhibit NKG2D co-activation of CTL. Nevertheless, the ability of PKA type I to inhibit NKG2D-mediated activation of NK and  T cells, strongly suggests that PGE 2 will inhibit NKG2D signaling in CTL since previous studies demonstrated that the increase of cAMP mediated by PGE 2 leads to PKA type I activation in these cells [29,48].…”
mentioning
confidence: 99%